The Septuagint of Proverbs: Jewish and/or Hellenistic Proverbs? ; Concerning the Hellenistic colouring of LXX Proverbs - Cook, Johann (Supplements to Vetus Testamentum, 1997)
Preliminary material /Johann Cook -- Chapter One: Introduction /Johann Cook -- Chapter Two: Analysis of Selected Chapters from Proverbs /Johann Cook -- Chapter Three: Conclusions /Johann Cook -- Chapter Four: Excursus Semantic Study of Specific Lexemes /Johann Cook -- Selected Bibliography /Johann Cook -- Modern Authors Index /Johann Cook -- Subject Index /Johann Cook -- Indices of Hebrew Words /Johann Cook -- Indices of Greek Words /Johann Cook -- Indices of Syriac Words /Johann Cook -- Biblical Reference Index /Johann Cook.